TRANSLATION UNITS - Nurmuhammadova Mukhlisakhan; Akhmedov Azimjon (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation. In the field of translation studies, the concept of translation units is fundamental. Translation units are segments of a source text that a translator processes as a single unit during the translation process. These units can vary greatly in size, ranging from individual words to phrases, sentences, or even larger sections of text. Understanding translation units is crucial for both theoretical and practical aspects of translation, as it influences the translator's approach to rendering meaning from one language to another. This article given information about translation units.